Induction of vascular GTP-cyclohydrolase I and endogenous tetrahydrobiopterin synthesis protect against inflammation-induced endothelial dysfunction in human atherosclerosis. - Antoniades, C; Cunnington, C; Antonopoulos, A; Neville, M; Margaritis, M; Demosthenous, M; Bendall, J; Hale, A; Cerrato, R; Tousoulis, D; Bakogiannis, C; Marinou, K; et al. (2011)
BACKGROUND: The endothelial nitric oxide synthase cofactor tetrahydrobiopterin (BH4) is essential for maintenance of enzymatic function. We hypothesized that induction of BH4 synthesis might be an endothelial defense mechanism against inflammation in vascular disease states. METHODS AND RESULTS: In Study 1, 20 healthy individuals were randomized to receive Salmonella typhi vaccine (a model of acute inflammation) or placebo in a double-blind study. Vaccination increased circulating BH4 and interleukin 6 and induced endothelial dysfunction (as evaluated by brachial artery flow-mediated dilation) after 8 hours. In Study 2, a functional haplotype (X haplotype) in the GCH1 gene, encoding GTP-cyclohydrolase I, the rate-limiting enzyme in biopterin biosynthesis, was associated with endothelial dysfunction in the presence of high-sensitivity C-reactive protein in 440 coronary artery disease patients. In Study 3, 10 patients with coronary artery disease homozygotes for the GCH1 X haplotype (XX) and 40 without the haplotype (OO) underwent S Typhi vaccination. XX patients were unable to increase plasma BH4 and had a greater reduction of flow-mediated dilation than OO patients. In Study 4, vessel segments from 19 patients undergoing coronary bypass surgery were incubated with or without cytokines (interleukin-6/tumor necrosis factor-α/lipopolysaccharide) for 24 hours. Cytokine stimulation upregulated GCH1 expression, increased vascular BH4, and improved vasorelaxation in response to acetylcholine, which was inhibited by the GTP-cyclohydrolase inhibitor 2,4-diamino-6-hydroxypyrimidine. CONCLUSIONS: The ability to increase vascular GCH1 expression and BH4 synthesis in response to inflammation preserves endothelial function in inflammatory states. These novel findings identify BH4 as a vascular defense mechanism against inflammation-induced endothelial dysfunction.